State of the art of bio-hydrogen production from biomass - Fakhru'l-Razi, A.; El-Mahdi, A. H.; Luqman Chuah, T. G. A. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/